Train-The-Trainer: A Generic Offer-And-Use Model for the Development of Trainers - Susanne Wisshak; Pia Schäfer; Leo van Waveren (International Journal of Training and Development, 2025)
This article is based on the premise that the international scientific community needs a generic theoretical framework to explain the determinants and mechanisms associated with learning opportunities for trainers in the field of training and development. Therefore, we adapted offer-and-use models for the continuous training of schoolteachers to trainers. We also incorporated the concept of the transfer of training into the model. The transfer of acquired knowledge and skills from the learning context to the work context represents an important criterion for training effectiveness. Since train-the-trainer programmes should also adhere to this criterion, our proposed model incorporates theoretical and empirical findings regarding transfer-enhancing measures drawn from both general training and development and the continuous education of schoolteachers. The theoretical model includes external factors (the train-the-trainer programme); individual factors (the participating trainers); contextual factors (the trainers' workplaces); the perception, interpretation, and use of learning opportunities; and learning processes of the trainers. These factors ultimately affect training outcomes at different levels (reactions, learning, transfer, and results). This model can be used to support long-needed scientific investigations of the determinants underlying train-the-trainer programmes as well as the quality of those qualifications. It also has considerable implications with respect to the conceptualisation and evaluation of such programmes in practice.
Keywords: 650; conceptual framework; offer-and-use model; train-the-trainer; training and development of trainers; training effectiveness; transfer of training